Advances in Software Engineering Techniques 4th IFIP TC 2 Central and East European Conference on Software Engineering Techniques, CEE-SET 2009, Krakow, Poland, October 12-14, 2009. Revised Selected Papers - Szmuc, Tomasz; Szpyrka, Marcin; Zendulka, Jaroslav; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th IFIP TC2 Central and East European Conference on Software Engineering Techniques, CEE-SET 2009, held in Krakow, Poland, in October 2009. The 19 revised full papers presented were carefully reviewed and selected from 63 submissions. The papers are organized in topical sections on software architectures and development; modelling and formal methods in software development; measurements, testing, and quality of software.
Keywords: Computer science; Computer communication systems; Computer programming; Software engineering; Programming languages (Electronic computers).; Computer logic; Computer Science; Software Engineering; Computer Communication Networks; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Programming Techniques; Information Systems Applications (incl. Internet).; Electronic books